Isolation and Characterization of RNA-Directed DNA Polymerase from a B-Type RNA Tumor Virus - Dion, Arnold S. (1974)
RNA-directed DNA polymerase was isolated from milk-borne B-type murine mammary tumor virus of the RIII mouse strain. The several hundred-fold-purified enzyme sediments at 5.5 to 5.7S with an average molecular weight of approximately 100,000. The purified enzyme is completely template dependent and responds to RNA, DNA, and synthetic templates. Stability studies indicate differential lability dependent on the exogenous template used to monitor activity.